Temporal trends of catheter ablation procedures in patients with atrial fibrillation and atrial flutter : A nationwide cohort study - Lappalainen, Antti; Hartikainen, Juha E.K.; Teppo, Konsta; Halminen, Olli; Aro, Aapo L.; Siponen, Rasmus; Virrankorpi, Janne; Marjamaa, Annukka; Salmela, Birgitta; Putaala, Jukka; Mustonen, Pirjo; Linna, Miika; et al. (Elsevier BV, 2025)
Background
Catheter ablation is a well-established treatment to prevent atrial fibrillation (AF) and atrial flutter (AFL) recurrences and to relieve symptoms, whereas pacemaker implantation and atrioventricular node (AVN) ablation is used for rate control when medical therapy fails.
Aims
We investigated temporal trends and patient characteristics in catheter ablation procedures for AF, AFL and AVN in Finland between 2012–2018.
Methods
Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) is a registry-based study including all patients with AF or AFL in Finland between 2012–2018.
​​​​​​​
Results
The number of patients with AF or AFL diagnosis in Finland increased from 185 057 to 243 802 between 2012–2018 and a total of 8954 first-time catheter ablation procedures were performed. Of them, 4909 (54.8 %) were AF ablations, 2731 (30.5 %) AFL ablations and 1314 (14.7 %) AVN ablations. The procedural numbers increased from 457/year to 934/year for AF, from 223/year to 553/year for AFL and from 114/year to 238/year for AVN. Altogether, 0.65% of all patients with diagnosed AF or AFL underwent AF, AFL or AVN ablation in 2018. The mean age of the patients increased in all ablation groups. Patients undergoing AF and AFL ablations were predominantly men (69.7 % and 74.6 % respectively) whereas patients undergoing AVN ablation were more often women (56.9%).
Conclusions
The use of catheter ablation more than doubled during 2012–2018 and the increase was particularly seen in the elderly patients. Nevertheless, only a minority of AF and AFL patients were treated with catheter ablations.